Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Reflecting on the Science of Climate Tipping Points to Inform and Assist Policy Making and Address the Risks they Pose to Society - T. F. Stocker; R. G. Jones; M. I. Hegglin; T. M. Lenton; G. C. Hegerl; S. I. Seneviratne; N. van der Wel; R. A. Wood (Surveys in Geophysics, 2025)
There is a diverging perception of climate tipping points, abrupt changes and surprises in the scientific community and the public. While such dynamics have been observed in the past, e.g., frequent reductions of the Atlantic meridional overturning circulation during the last ice age, or ice sheet collapses, tipping points might also be a possibility in an anthropogenically perturbed climate. In this context, high impact—low likelihood events, both in the physical realm as well as in ecosystems, will be potentially dangerous. Here we argue that a formalized assessment of the state of science is needed in order to establish a consensus on this issue and to reconcile diverging views. This has been the approach taken by the Intergovernmental Panel on Climate Change (IPCC). Since 1990, the IPCC has consistently generated robust consensus on several complex issues, ranging from the detection and attribution of climate change, the global carbon budget and climate sensitivity, to the projection of extreme events and their impact. Here, we suggest that a scientific assessment on tipping points, conducted collaboratively by the IPCC and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services, would represent an ambitious yet necessary goal to be accomplished within the next decade.

Appetite, food intake, and gut hormone responses to glycomacropeptide protein ingestion in older adults: A feasibility, acceptability, and pilot study - Jordan Warner; Rachel Stocker; Kirsten Brandt; Daniel R. Crabtree; Lindsey Ormond; Emma Stevenson; Adrian Holliday (Appetite, 2024)

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

A new short-faced archosauriform from the Upper Triassic Placerias/Downs’ quarry complex, Arizona, USA, expands the morphological diversity of the Triassic archosauriform radiation - Andrew B. Heckert; Sterling J. Nesbitt; Michelle R. Stocker; Vince P. Schneider; Devin K. Hoffman; Brian W. Zimmer (The Science of Nature, 2021)
The Placerias /Downs’ Quarry complex in eastern Arizona, USA, is the most diverse Upper Triassic vertebrate locality known. We report a new short-faced archosauriform, Syntomiprosopus sucherorum gen. et sp. nov., represented by four incomplete mandibles, that expands that diversity with a morphology unique among Late Triassic archosauriforms. The most distinctive feature of Syntomiprosopus gen. nov. is its anteroposteriorly short, robust mandible with 3–4 anterior, a larger caniniform, and 1–3 “postcanine” alveoli. The size and shape of the alveoli and the preserved tips of replacement teeth preclude assignment to any taxon known only from teeth. Additional autapomorphies of S. sucherorum gen. et sp. nov. include a large fossa associated with the mandibular fenestra, an interdigitating suture of the surangular with the dentary, fine texture ornamenting the medial surface of the splenial, and a surangular ridge that completes a 90° arc. The external surfaces of the mandibles bear shallow, densely packed, irregular, fine pits and narrow, arcuate grooves. This combination of character states allows an archosauriform assignment; however, an associated and similarly sized braincase indicates that Syntomiprosopus n. gen. may represent previously unsampled disparity in early-diverging crocodylomorphs. The Placerias Quarry is Adamanian (Norian, maximum depositional age ~219 Ma), and this specimen appears to be an early example of shortening of the skull, which occurs later in diverse archosaur lineages, including the Late Cretaceous crocodyliform Simosuchus . This is another case where Triassic archosauriforms occupied morphospace converged upon by other archosaurs later in the Mesozoic and further demonstrates that even well-sampled localities can yield new taxa.

Intraseasonal variation of phycocyanin concentrations and environmental covariates in two agricultural irrigation ponds in Maryland, USA - J. E. Smith; M. D. Stocker; J. L. Wolny; R. L. Hill; Y. A. Pachepsky (Environmental Monitoring and Assessment, 2020)

Cutting Through the Noise: Bacterial Chemotaxis in Marine Microenvironments - Douglas R. Brumley; Francesco Carrara; Andrew M. Hein; George I. Hagstrom; Simon A. Levin; Roman Stocker (Frontiers in Marine Science, 2020)

Manure Consistency and Weathering Affect the Removal of Fecal Indicator Bacteria from Grass-Covered Soil - M. D. Stocker; R. L. Hill; Y. A. Pachepsky (Water, Air, & Soil Pollution, 2020)

Sodium-glucose cotransporter 2 inhibitors for type 2 diabetes—cardiovascular and renal benefits in patients with chronic kidney disease - Tamara Y. Milder; Sophie L. Stocker; Dorit Samocha-Bonet; Richard O. Day; Jerry R. Greenfield (European Journal of Clinical Pharmacology, 2019)

The paleobiogeographical significance of the Silurian and Devonian trilobites of Japan - Christopher P. Stocker; Derek J. Siveter; Philip D. Lane; Mark Williams; Tatsuo Oji; Simon R. Wallis; Gengo Tanaka; Toshifumi Komatsu; David J. Siveter; Thijs R. A. Vandenbroucke (Island Arc, 2019)
Six major groups of trilobites from the Silurian and Devonian of Japan are evaluated for their paleobiogeographical signature. Silurian illaenids and scutelluids show four generic‐level and at least two species‐level links with the Australian segment of the Gondwana paleocontinent; encrinurids also indicate two generic‐level links with Australia and also the South China paleocontinent; whilst Devonian phacopids, and possibly proetids, suggest at least two generic‐level links with the North China paleocontinent. These different patterns may reflect the fragmentary biostratigraphical record of Japanese trilobites, but they also appear to reflect paleoenvironmental parameters associated with lithofacies, and paleoecology. Thus, Japanese assemblages of proetids and phacopids occurring in deep‐water clastic lithofacies have counterparts in similar settings in North China, and Japanese scutelluids and illaenids are strongly associated with shallow marine carbonate lithofacies that are similar to those of their occurrences in Australia. Japanese encrinurids occur in carbonate rocks indicative of shallow marine settings in the Kurosegawa Terrane, and they demonstrate a consistent paleobiogeographical affinity with Australia and South China. Larval ecology cannot be directly assessed for Japanese trilobite groups. However, proetids have consistently been shown to have planktonic protaspides, whereas illaenids, scutelluids, and encrinurids have benthic protaspides. Planktonic protaspides would have a greater propensity for distribution in ocean currents than benthic ones, and therefore may be of more limited paleobiogeographical utility. The combined data from the six different groups indicates that the complex paleobiogeographical patterns of the Japanese trilobite assemblages need to be interpreted with caution, and similarity of taxa does not necessarily denote paleogeographical proximity to other regions.

Functional Evaluation of Three Manure-Borne Indicator Bacteria Release Models with Multiyear Field Experiment Data - M. Stocker; A. Yakirevich; A. Guber; G. Martinez; R. Blaustein; G. Whelan; D. Goodrich; D. Shelton; Y. Pachepsky (Water, Air, & Soil Pollution, 2018)

A new armored archosauriform (Diapsida: Archosauromorpha) from the marine Middle Triassic of China, with implications for the diverse life styles of archosauriforms prior to the diversification of Archosauria - Chun Li; Xiao-chun Wu; Li-jun Zhao; Sterling J. Nesbitt; Michelle R. Stocker; Li-Ting Wang (The Science of Nature, 2016)

Irrigation waters and pipe-based biofilms as sources for antibiotic-resistant bacteria - Ryan A. Blaustein; Daniel R. Shelton; Jo Ann S. Van Kessel; Jeffrey S. Karns; Matthew D. Stocker; Yakov A. Pachepsky (Environmental Monitoring and Assessment, 2016)

Direct evidence of trophic interactions among apex predators in the Late Triassic of western North America - Stephanie K. Drumheller; Michelle R. Stocker; Sterling J. Nesbitt (The Science of Nature, 2014)

β2-adrenoceptor agonists can both stimulate and inhibit glucose uptake in mouse soleus muscle through ligand-directed signalling - Robert A. Ngala; Jacqueline F. O’Dowd; Claire J. Stocker; Michael A. Cawthorne; Jonathan R. S. Arch (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Scenarios for investigating risks to biodiversity - Joachim H. Spangenberg; Alberte Bondeau; Timothy R. Carter; Stefan Fronzek; Jill Jaeger; Kirsti Jylhä; Ingolf Kühn; Ines Omann; Alex Paul; Isabelle Reginster; Mark Rounsevell; Oliver Schweiger; et al. (Global Ecology and Biogeography, 2012)
Aim This paper describes a set of integrative scenarios developed in the ALARM (Assessing LArge‐scale environmental Risks for biodiversity with tested Methods) project. The ultimate aim of ALARM was to develop and test methods and protocols for the assessment of large‐scale environmental risks to biodiversity and to evaluate mitigation options. Scenarios provide a tool for exploring such risks and the policy options to mitigate them; therefore they play a central role within the ALARM project. Methods Three integrative scenarios (liberalization, business as might be usual, sustainability) were developed and illustrated using the econometric model described in a subsequent paper. They are contextualized with projections from climate models and provide the input for model‐based assessments of biodiversity trends. Additionally, three shock scenarios were developed (Gulf Stream collapse, peak oil, pandemic) to demonstrate the limits of linear extrapolation. As these extend beyond model capabilities, they are discussed semi‐quantitatively based on modelling insights. Results Although the policy impacts on biodiversity are different for different pressures, biomes and species groups, some general trends could be identified. An extension of current EU policies will act as a brake on current trends by slowing down the loss of biodiversity in many cases and in most biomes, but it will be capable of neither halting nor of reversing the loss. Liberalization has the effect of accelerating biodiversity loss across the board, with few exceptions. A coherent sustainability scenario is clearly the most effective at preserving biodiversity, but the variant tested here still does not halt losses in all cases. Main conclusions Current EU policies for protecting biodiversity appear to be insufficient to reverse ongoing losses. Coherent sustainability strategies are effective at conserving biodiversity, but in order to assess losses and then reverse them, measures would need to be introduced that extend beyond the steps tested in the ALARM sustainability scenario.

The IPCC AR5 guidance note on consistent treatment of uncertainties: a common approach across the working groups - Michael D. Mastrandrea; Katharine J. Mach; Gian-Kasper Plattner; Ottmar Edenhofer; Thomas F. Stocker; Christopher B. Field; Kristie L. Ebi; Patrick R. Matschoss (Climatic Change, 2011)

The influence of regional circulation patterns on wet and dry mineral dust and sea salt deposition over Greenland - M. A. Hutterli; T. Crueger; H. Fischer; K. K. Andersen; C. C. Raible; T. F. Stocker; M. L. Siggaard-Andersen; J. R. McConnell; R. C. Bales; J. F. Burkhart (Climate Dynamics, 2007)

The coupling of optimal economic growth and climate dynamics - Olivier Bahn; Laurent Drouet; Neil R. Edwards; Alain Haurie; Reto Knutti; Socrates Kypreos; Thomas F. Stocker; Jean-Philippe Vial (Climatic Change, 2006)

The association between inversion In(3R)Payne and clinally varying traits in Drosophila melanogaster - L. Rako; A. R. Anderson; C. M. Sgrò; A. J. Stocker; A. A. Hoffmann (Genetica, 2006)

The Effects of Temperature Shock on Transcription and Replication in Rhynchosciara americana (Diptera: Sciaridae) - Ann Jacob Stocker; Christiane R. G. Madalena; Eduardo Gorab (Genetica, 2006)

Probabilistic climate change projections using neural networks - R. Knutti; T. F. Stocker; F. Joos; G.-K. Plattner (Climate Dynamics, 2003)

Modeling circulation in lakes: Spatial and temporal variations - Bernard Laval; Jörg Imberger; Ben R. Hodges; Roman Stocker (Limnology and Oceanography, 2003)
The influence of spatial and temporal variations in wind forcing on the circulation in lakes is investigated using field data and the three‐dimensional Estuary and Lake Computer Model (ELCOM) applied to Lake Kinneret. Lake Kinneret field data from six thermistor chains and eight wind anemometers deployed during July 2001 are presented. Internal wave motions are well reproduced by the numerical model when forced with a spatially uniform wind taken from a station near the lake center; however, simulated seiche amplitudes are too large (especially vertical mode 2) and lead observations by 3–10 h (for a 24‐h period wave) at different locations around the lake. Consideration of the spatial variation of the wind field improves simulated wave amplitude, and phase error at all stations is reduced to less than 1.5 h. This improvement is attributable to a better representation of the horizontally averaged wind stress and can be reproduced with a spatially uniform wind that has the same horizontally averaged wind stress as the spatially varying wind field. However, a spatially varying wind field is essential for simulating mean surface circulation, which is shown to be predominantly directly forced by the surface‐layer‐averaged wind stress moment.

Response: Sustainable Forestry and Certification Programs - J. Heissenbuttel; R. Cantrell; L. Stocker (Journal of Forestry, 2001)

Effect on Diphtheria Immunity of Combined Tetanus and Diphtheria Booster Vaccination in Adults - S. Marlovits; R. Stocker; A. Efstratiou; K. Broughton; A. Kaider; V. Vécsei; H. Kollaritsch (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

A field study of the effects of elevated CO 2 and plant species diversity on ecosystem‐level gas exchange in a planted calcareous grassland - R. Stocker; CH. Körner; B. Schmid; P. A. Niklaus; P. W. Leadley (Global Change Biology, 1999)
The relationship between plant species diversity and ecosystem CO 2 and water vapour fluxes was investigated for planted calcareous grassland communities composed of 5, 12, or 32 species assembled from the native plant species pool. These diversity manipulations were done in factorial combination with a CO 2 enrichment experiment in order to investigate the degree to which ecosystem responses to elevated CO 2 are altered by a loss of plant diversity. Ecosystem CO 2 and H 2 O fluxes were measured over several 24‐h periods during the 1994 and 1995 growing seasons. Ecosystem CO 2 assimilation on a ground area basis decreased with decreasing plant diversity in the first year and this was related to a decline in above‐ground plant biomass. In the second year, however, CO 2 assimilation was not affected by diversity, and this corresponded to the disappearance of a diversity effect on above‐ground biomass. Irrespective of diversity treatment, CO 2 assimilation on a ground area basis was linearly related to peak above‐ground biomass in both years. Elevated CO 2 significantly increased ecosystem CO 2 assimilation in both years with no interaction between diversity and CO 2 treatment, and no corresponding increase in above‐ground biomass. There were no significant effects of diversity on water vapour flux, which was measured only in the second year. There were indications of a small CO 2 effect on water vapour flux (3–9% lower at elevated CO 2 depending on the light level). Our findings suggest that decreasing plant species diversity may substantially decrease ecosystem CO 2 assimilation during the establishment of such planted calcareous grassland communities, but also suggest that this effect may not persist. In addition, we find no evidence that plant species diversity alters the response of ecosystem CO 2 assimilation to elevated CO 2 .

Barbiturate coma may promote reversible bone marrow suppression in patients with severe isolated traumatic brain injury - J. F. Stover; R. Stocker (European Journal of Clinical Pharmacology, 1998)